1984
DOI: 10.1017/s0021859600047274
|View full text |Cite
|
Sign up to set email alerts
|

Complete diets for dairy cows: the effect of energy concentration and change in energy concentration of a complete diet on intake and performance of lactating dairy cows

Abstract: Ninety-two British Friesians (56 cows and 36 heifers) were divided into two groups during weeks 3-10 of lactation and received ad libitum either complete diet H (65 % concentrates, 35% grass silage, 11-7 MJ ME/kg D.M.) or diet M (50% concentrates, 50% grass silage, 11-2 MJ ME/kg D.M.). In weeks 11-20 half the animals of each group continued to receive the same diet (HH or MM) while the other half were changed from diet H to M (HM) or from diet M to L (ML). Diet L contained 35 % concentrates, 65% grass silage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Proportions of propionate for all treatments numerically increased when the concentrate was delivered 2 h after concentrate was delivered. Similar to our results, Phipps et al (1984) reported no differences in proportions of acetate, propionate or butyrate when ingredients were combined or separated at restricted intake levels for dairy cattle. Also in agreement with our results, Yan et al (1998) found no differences in proportions of VFA or total VFA concentration when cows were fed a complete diet or separately fed the ingredients of that diet.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Proportions of propionate for all treatments numerically increased when the concentrate was delivered 2 h after concentrate was delivered. Similar to our results, Phipps et al (1984) reported no differences in proportions of acetate, propionate or butyrate when ingredients were combined or separated at restricted intake levels for dairy cattle. Also in agreement with our results, Yan et al (1998) found no differences in proportions of VFA or total VFA concentration when cows were fed a complete diet or separately fed the ingredients of that diet.…”
Section: Discussionsupporting
confidence: 90%
“…In cows fed ad libitum, DM digestion of a complete diet was reduced compared to cows fed the same ingredients separately ( Gordon et al, 1995 ). Improved DM and OM digestibility were also observed in cows fed separate ingredients compared to a TMR when intake was limited to 2.5% BW ( Phipps et al, 1984 ), although that degree of restriction is likely close to ad libitum feeding. The relatively higher feeding rates in these studies compared to the present study allowed some selectivity among separately fed ingredients, which resulted in improved digestibility when cattle were allowed separate access to ingredients.…”
Section: Discussionmentioning
confidence: 99%